Serum cholinesterase as a biomarker for sepsis-associated immunosuppression via Hub gene RORA - Qian He; Xu Huang (PLoS ONE, 2026)
Background Sepsis-induced immunosuppression is a key factor contributing to high mortality rates. However, suitable biomarkers for routine clinical monitoring of immune function are currently lacking. Serum cholinesterase levels are markedly diminished in sepsis and are associated with unfavorable prognoses, its role in the immunosuppression pathology and the mechanisms involved remain inadequately understood. Methods We conducted a translational study integrating clinical research, bioinformatics analysis and animal experiments. Initially, within a single-center clinical cohort, we investigated the correlation between serum cholinesterase levels and lymphocyte subsets in patients suffering from sepsis, subsequently evaluating its association with disease severity (APACHE-II and SOFA scores) and clinical outcomes. Subsequently, by integrating sepsis transcriptome data with cholinergic anti-inflammatory pathways and immune-related gene sets, we identified the hub gene RORA and validated it across multiple dimensions using public databases. Finally, in the CLP sepsis mouse model, we measured cholinesterase activity and specifically quantified RORA mRNA expression in the spleen. We then analyzed the correlation between these measurements and changes in key immune cell counts. Results Clinical data revealed significantly reduced serum cholinesterase activity in sepsis patients. Decreased cholinesterase levels positively correlated with elevated disease severity scores (APAChE-II, SOFA) and reduced counts of CD4 ⁺ T cells, CD8 ⁺ T cells, and NK cells. Bioinformatics analysis identified RORA as a hub gene linking sepsis, cholinesterase, and immune responses. Across eight independent GEO datasets, RORA expression exhibited a consistent downregulation trend in sepsis with high diagnostic value. Analysis of immune cell infiltration revealed significant positive correlations between RORA and counts of CD4 ⁺ T, CD8 ⁺ T, and NK cells in sepsis. In the CLP mouse model, reductions in spleen CD3 ⁺ T, CD4 ⁺ T, and CD8 ⁺ T cell counts coincided with notable decreases in serum cholinesterase and spleen RORA mRNA levels. Both serum cholinesterase concentration and spleen RORA mRNA expression exhibited positive correlations with CD4 ⁺ T and CD8 ⁺ T cell counts. Conclusion This study establishes serum cholinesterase as a valuable clinical biomarker for assessing sepsis diagnosis, disease severity, and immunosuppression. For the first time, through multiomics integration and experimental validation, RORA has been identified as the key molecular bridge linking the cholinesterase activity and immunosuppression in sepsis. This not only provides a new direction for understanding immune dysregulation in sepsis but also lays a theoretical foundation for the future development of RORA-targeted immunomodulation and treatment strategies for sepsis.